2022
DOI: 10.1002/advs.202202470
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal Sensors with Decoupled Sensing Mechanisms

Abstract: Highly sensitive and multimodal sensors have recently emerged for a wide range of applications, including epidermal electronics, robotics, health‐monitoring devices and human–machine interfaces. However, cross‐sensitivity prevents accurate measurements of the target input signals when a multiple of them are simultaneously present. Therefore, the selection of the multifunctional materials and the design of the sensor structures play a significant role in multimodal sensors with decoupled sensing mechanisms. Hen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
124
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(124 citation statements)
references
References 115 publications
0
124
0
Order By: Relevance
“…Cheng and co-workers proposed a method to directly fabricate electronic devices on freeform surfaces using intense pulsed light-induced mass transfer, and deploying functional circuits on 3D freeform surfaces has greatly promoted the development of flexible wearable devices . Moreover, the functions of flexible wearable sensors are increasingly rich, and many flexible sensors for multi-modal detection have been developed . For example, Yang and co-workers reported a flexible sensor for underwater motion monitoring that simultaneously detects strain and temperature .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cheng and co-workers proposed a method to directly fabricate electronic devices on freeform surfaces using intense pulsed light-induced mass transfer, and deploying functional circuits on 3D freeform surfaces has greatly promoted the development of flexible wearable devices . Moreover, the functions of flexible wearable sensors are increasingly rich, and many flexible sensors for multi-modal detection have been developed . For example, Yang and co-workers reported a flexible sensor for underwater motion monitoring that simultaneously detects strain and temperature .…”
Section: Introductionmentioning
confidence: 99%
“…5 Moreover, the functions of flexible wearable sensors are increasingly rich, and many flexible sensors for multi-modal detection have been developed. 6 For example, Yang and coworkers reported a flexible sensor for underwater motion monitoring that simultaneously detects strain and temperature. 7 Therefore, the development of high-performance and multifunctional flexible pressure sensors is imminent.…”
Section: Introductionmentioning
confidence: 99%
“…They have been extensively investigated in recent years, and tremendous amounts of research results have been reported all over the world. 17 For example, low-cost pressure sensors based on MXene nanosheets and papers are reported by Fu et al 18 and Gao et al 19 Multimodal sensors with decoupled sensing mechanisms are reported by Shin et al 20 and Yang et al 21 According to the sensing mechanism, they could be primarily classified into the resistive type and the capacitive type. 22 Resistive pressure sensors have the advantages of high sensitivity, large linear working range, and good response stability synchronously.…”
Section: Introductionmentioning
confidence: 99%
“…[6] Despite some progress, existing multimodal sensing technologies assemble various sensors based on different sensing principles, resulting in bulky system designs, cumbersome signal interfaces, and complex data processing procedures. [7] These technologies cannot meet the growing complex environment perception demands of miniaturized devices, such as microrobots [8] and in vivo medical devices. [9] Thus, a miniature multimodal sensing platform is urgently needed.…”
Section: Introductionmentioning
confidence: 99%